Correction: Chen et al. Sex Difference in Cigarette-Smoking Status and Its Association with Brain Volumes Using Large-Scale Community-Representative Data. Brain Sci. 2023, 13, 1164 - Xiaofei Chen; Riley Cook; Francesca M. Filbey; Hang Nguyen; Roderick McColl; Haekyung Jeon-Slaughter (Brain Sciences)
In the original publication [...]